2012
DOI: 10.1109/tsp.2012.2200476
|View full text |Cite
|
Sign up to set email alerts
|

Noncoherent OSTBC-OFDM for MIMO and Cooperative Communications: Perfect Channel Identifiability and Achievable Diversity Order

Abstract: This paper considers the context of orthogonal space-time block coded OFDM (OSTBC-OFDM) without channel state information at the receiver. Assuming noncoherent maximum-likelihood detection, the interest herein lies in detection within one OSTBC-OFDM block, motivated by its capability of accommodating relatively fast block fading channels. Our investigation focuses on analysis aspects, where we seek to establish practical noncoherent BPSK/QPSK OSTBC-OFDM schemes that have provably good channel identifiability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 46 publications
(125 reference statements)
0
21
0
Order By: Relevance
“…Thus the upper bound of the original network's outage probability is obtained by calculating the system outage probability of this special symmetric network using (24). Similarly, we can generate the second symmetric network where the source-to-relay links are guaranteed to have higher/equal qualities than/to the corresponding links in the original network, namely we have λ…”
Section: Discussionmentioning
confidence: 99%
“…Thus the upper bound of the original network's outage probability is obtained by calculating the system outage probability of this special symmetric network using (24). Similarly, we can generate the second symmetric network where the source-to-relay links are guaranteed to have higher/equal qualities than/to the corresponding links in the original network, namely we have λ…”
Section: Discussionmentioning
confidence: 99%
“…In the first subsection, we review some transmission schemes reported in [14]- [16] that can guarantee unique data identification, i.e., guarantee the codeword c to be uniquely decoded by the noncoherent ML decoder (10) in the noise-free situation. In the second subsection, we present our main results on the diversity order of the noncoherent ML decoder (10).…”
Section: Unique Data Identifiability and Diversity Analysismentioning
confidence: 99%
“…The noncoherent techniques are appealing because they use only a few number of pilots, or even no pilot, for data detection and channel estimation, and thus have great potential for deployment under fast time-varying channels. However, most of the existing works focus on two separate scenarios, namely, coded flat-fading space-time systems (no OFDM) [9]- [11] and uncoded OSTBC-OFDM systems (no channel coding) [12]- [16]. While it is possible to extend the works in [9], [10] to coded OSTBC-OFDM by considering each OFDM subcarrier as an individual flat-fading channel, such natural extension requires the channel to remain static over a large number of OFDM blocks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations